2016
DOI: 10.1111/nph.14200
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic regulation of the transcription factor ABORTED MICROSPORES (AMS) is essential for tapetum and pollen development in Arabidopsis

Abstract: Summary Viable pollen is essential for plant reproduction and crop yield. Its production requires coordinated expression at specific stages during anther development, involving early meiosis‐associated events and late pollen wall formation. The ABORTED MICROSPORES (AMS) transcription factor is a master regulator of sporopollenin biosynthesis, secretion and pollen wall formation in Arabidopsis. Here we show that it has complex regulation and additional essential roles earlier in pollen formation.An inducible‐AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 40 publications
2
85
0
Order By: Relevance
“…Previous studies have shown that TDF1 alone is sufficient to activate the expression of genes required for pollen wall synthesis (Gu et al ., ), suggesting that DYT1–TDF1–AMS can maintain normal pollen wall formation via TDF1 regulation after DYT1 decreases, which is supported by the short‐term expression of the DYT1‐GFP protein in the tapetum (Gu et al ., ). The FFL of TDF1–AMS–MS188 may prolong the time during which MS188 is transcribed, which is consistent with the two peaks of the MS188 expression pattern in stages 6–8, during which the second peak of MS188 is higher than the first peak (Ferguson et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have shown that TDF1 alone is sufficient to activate the expression of genes required for pollen wall synthesis (Gu et al ., ), suggesting that DYT1–TDF1–AMS can maintain normal pollen wall formation via TDF1 regulation after DYT1 decreases, which is supported by the short‐term expression of the DYT1‐GFP protein in the tapetum (Gu et al ., ). The FFL of TDF1–AMS–MS188 may prolong the time during which MS188 is transcribed, which is consistent with the two peaks of the MS188 expression pattern in stages 6–8, during which the second peak of MS188 is higher than the first peak (Ferguson et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Bars, 20 lm. Considering that the expression of direct AMS targets that are responsible for tapetum development and pollen wall formation are required as additional factors for activation, regardless of the functional AMS presence (Ferguson et al, 2017), we speculated that TDF1 and AMS are involved in this downstream transcription network by forming heterodimers. To find out if TDF1 has the ability to bind to targets of AMS, we assayed the enrichments of the MS188 and TEK genes in the tdf1 À/À gpTDF1:TDF1-GFP lines via a ChIP analysis.…”
Section: Tdf1 Interacts With Ams In Vivomentioning
confidence: 99%
“…AMS is a key regulator of sporopollenin biosynthesis, secretion, and pollen wall formation and can form a complex with MS188/MYB103/ MYB80 that likely activates the expression of CYP703A2 and MS1 encoding a transcription factor (Xu et al, 2010Zhu et al, 2011;Feng et al, 2012;Gu et al, 2014;Xiong et al, 2016;Ferguson et al, 2017). DYT1 and MYB35/TDF1 are required for the development of tapetum and reproductive cells at early stages, as supported by the findings that DYT1 and MYB35/TDF1 mutants exhibit abnormal tapetal cells at anther stage 5 and onward and that their anthers lack any pollen (Zhang et al, 2006;Zhu et al, 2008;Gu et al, 2014).…”
Section: Cle19 Functions As a Negative Regulator Of Ams-regulated Polmentioning
confidence: 99%
“…We firstly tested whether exogenous application of auxin to fruits of an infertile mutant could re-initiate the timely arrest of the PI. We treated sterile fruit in the ams mutant, which like ms1 fails to go through normal floral arrest [12], with the auxin analog NAA from 6 dpa. This resulted in earlier IM arrest with the PI producing ~50 fruit, compared to ~80 in mock-treated plants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Arabidopsis wild-types Col-0 and Ler were used as indicated. The following lines have previously been described before; ms1-1 (Ler background) [14]; AMS:AMS-GR ams (Col-0 background, ams is SALK_152147) [12]; MS1:MS1-GR ms1-1 (Ler background) [15].…”
Section: Plant Materialsmentioning
confidence: 99%